Using Neural Network Method to Solve Marker Making Calculation of Fabric Lays Quantities Efficiency for Optimum Result in the Apparel Industry - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Using Artificial Neural Network (ANN) method aims to obtain the highest productivity for calculation of fabric lays quantities process in cutting department of apparel industry. The calculations of fabric lays quantities (FLQC) provide us with the exact length of the marker making. Fitting the marker making with spreading table and at the same time the possibility of spreading more than one marker making on the same table, shows the importance of estimating the length of the marker making (MM). A system was created by applying the ANN methods to marker making length data used in the industry. Using different possible calculations of fabric lays quantities findings, marker making lengths are approximated resulting in that the most optimum calculations of fabric lays quantities have been decided.
Keywords: Apparel Industry; calculating of fabric lays quantities; marker making length; Artificial Neural Network; back propagation algorithm